2018
DOI: 10.1136/heartjnl-2017-312867
|View full text |Cite
|
Sign up to set email alerts
|

Aortic elongation part II: the risk of acute type A aortic dissection

Abstract: Ascending aortic length could serve as an independent predictor for ATAAD. Future studies addressing indications for prophylactic surgery should also investigate aortic length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…This evolution has paved the way for more comprehensive radiological measurements, such as those of aortic length and volume shown here. Previous studies investigating vessel length have demonstrated that the healthy aorta gradually elongates with age and that the dissected aorta is notably longer than would have been expected based on age, gender and body surface area (BSA) 12–14 21–23. The current work adds to this knowledge by revealing that aortic length also serves as more discriminative ATAAD predictor than the maximal transverse diameter.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This evolution has paved the way for more comprehensive radiological measurements, such as those of aortic length and volume shown here. Previous studies investigating vessel length have demonstrated that the healthy aorta gradually elongates with age and that the dissected aorta is notably longer than would have been expected based on age, gender and body surface area (BSA) 12–14 21–23. The current work adds to this knowledge by revealing that aortic length also serves as more discriminative ATAAD predictor than the maximal transverse diameter.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, measurements of aortic volume and length could provide additional information over diameters with regard to the detection of aneurysm progression. Whereas the predictive value of aortic volumetry has not yet been investigated, several studies have evaluated the potential role of excessive vessel lengthening in the pathophysiology of dissection 12–14. Although all of these studies reported that patients with ATAAD had elongated ascending aortas when compared with healthy controls, these reports mainly included postdissection measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with type A aortic dissection have a longer ascending aorta than do healthy people [3]. Ascending aortic length per centimeter was reported to have an odds ratio of 5.3 for ascending aortic dissection [4]. However, these studies were cross-sectional studies, and the exact longitudinal change of aortic length was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Over-diagnosis results in needless patient anxiety and excessive sequential imaging. Rather than using aortic diameter thresholds derived from younger populations, we should focus on identifying which patients are at risk of aortic dissection; possibly by considering aortic length, not just diameter, or by increased attention to genetic and clinical risk factors, including hypertension 4 5. In the accompanying editorial, Groepenhoff and den Ruijter6 point out several other differences in vascular properties between men and women related to coronary, carotid and aortic disease (figure 3).…”
mentioning
confidence: 99%